Pengaruh Budaya Organisasi dan Kepuasan Kerja terhadap Organizational Citizenship Behavior Melalui Komitmen Organisasi Sebagai Intervening Pada Pegawai Instansi XYZ - Tri Nuryani, Fajar; Djamil, Masydzulhak (Jurnal Ekonomi Manajemen Sistem Informasi, 2024)
This research aims to strengthen the results of previous research and conduct an analysis of the influence of Organizational Culture and Job Satisfaction on Organizational Citizenship Behavior through Organizational Commitment as an intervention for XYZ Agency Employees. Sampling in this study used a non-probability sampling technique with a purposive sampling technique of 187 respondents. The strategy applied in checking information is SmartPLS v.3.2.9. The research results show that Hierarchical Culture has an impact on OCB, Job Fulfillment influences OCB, Authoritative Culture basically influences Authoritative Responsibility, Job Fulfillment influences Hierarchical Responsibility, Authoritative Responsibility has a positive and large influence on OCB, Hierarchical Culture influences OCB through the mediation of Authoritative Responsibility , and Job Fulfillment fundamentally influence OCB through the mediation of Hierarchical Responsibilities.